2018
DOI: 10.1016/j.amjsurg.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The negative effect of perioperative red blood cell transfusion on morbidity and mortality after major abdominal operations

Abstract: Perioperative blood transfusion is independently associated with an increased risk of morbidity and mortality after most major abdominal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Severe anemia and massive bleeding are critical condition associated with various unfavorable outcomes, and allogenic blood transfusion is the most common treatment [20,2830]. However, numerous studies have found that PRBC transfusion was associated with adverse short- and long-term outcomes, especially in surgery patients when transfused perioperatively or intraoperatively [1215].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe anemia and massive bleeding are critical condition associated with various unfavorable outcomes, and allogenic blood transfusion is the most common treatment [20,2830]. However, numerous studies have found that PRBC transfusion was associated with adverse short- and long-term outcomes, especially in surgery patients when transfused perioperatively or intraoperatively [1215].…”
Section: Discussionmentioning
confidence: 99%
“…However, overutilization of FPC is common, since there is no consensus on the optimal indication and threshold for utilization of FPC. Perioperative or intraoperative transfusion of FFP and platelet has been found to increase the risk of postoperative complications in several studies but not in others [13,1820].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous retrospective studies, perioperative blood transfusions were associated with poor prognosis after surgery for cancer, and were a major independent risk factor for postoperative bacterial infection [16,17]. Patients receiving intraoperative blood transfusion often have anemia before operation or large intraoperative blood loss during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic gastrointestinal resection includes small bowel and colon resections. These operations were highly associated with a red blood cell (RBC) transfusion (2). Inflammation is a nonspecific response of the organism to endogenous or exogenous stimulants to maintain the survival.…”
Section: Introductionmentioning
confidence: 99%